THE EFFECT OF UNDERSTANDING CORRUPTION ON ANTI-CORRUPTION ATTITUDES IN IMPROVING SELF INTEGRITY IN CIVICS STUDENTS OF FKIP UMSU - Taufika, Ryan; Lubis, Hamidah Azzahra S; Kemala, Vinna Dinda; Sitepu, Melyani Sari; Panggabean, Nauraini Rusyid (Program Pascasarjana UIN Sumatera Utara, 2026)
Corruption is a serious challenge that threatens the academic integrity and character of students as future leaders. Efforts to eradicate corruption require a comprehensive and innovative approach, including optimization in learning and societal practices. The purpose of this study is to analyze the relationship between students' understanding of corruption on anti-corruption attitudes and their contribution in improving self-integrity in students of the Pancasila and Citizenship Education (PPKn) Study Program, FKIP UMSU. The research method used in this study uses a quantitative approach with a descriptive correlational design. Data were collected through closed questionnaires and semi-structured interviews with 60 active student respondents in the 4th and 6th semesters. The results showed that students' understanding of corruption was high. There is a significant positive relationship between this level of understanding and anti-corruption attitudes shown by students with a Pearson correlation coefficient of r = 0.672 (significant at p < 0.01) such as the courage to refuse gratuities, academic transparency, and reporting unethical actions. Further analysis also found that understanding corruption contributed substantially to strengthening students' personal integrity with a correlation coefficient of r = 0.596 (p < 0.01) especially in the aspects of morality, responsibility, and consistency between values and actions. The conclusion of this study shows that the integration of anti-corruption education in the curriculum and the strengthening of a clean and transparent academic culture are instrumental in preventing corruption in higher education.